Trust me, I'm a doctor: A PhD survival guide - Koen Deconinck (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
So, you've decided to do a PhD ... now what? In this essay, I provide some advice for beginning PhD students - basically sharing with you what I would tell my younger self. Doing a PhD is a transformative experience, but the process is challenging - not merely on an intellectual level but also psychologically. To overcome these challenges you will need a certain mindset and a bag of tricks. I offer some help to get you in the right mindset, and I share some of my own tricks for studying, research, and productivity in general.
Keywords: 330